STEERing an IDeA in Undergraduate Research at a Rural Research Intensive University - Donald A. Sens; Karen L. Cisek; Scott H. Garrett; Seema Somji; Jane R. Dunlevy; Mary Ann Sens; Pat Conway; Van A. Doze (Elsevier, 2017)
This study documents outcomes, including student career choices, of the North Dakota Institutional Development Award Networks of Biomedical Research Excellence program that provides 10-week, summer undergraduate research experiences at the University of North Dakota School of Medicine and Health Sciences. Program evaluation initiated in 2008 and, to date, 335 students have completed the program. Of the 335, 214 students have successfully completed their bachelor's degree, 102 are still undergraduates, and 19 either did not complete a bachelor's degree or were lost to follow-up. The program was able to track 200 of the 214 students for education and career choices following graduation. Of these 200, 76% continued in postgraduate health-related education; 34.0% and 20.5% are enrolled in or have completed MD or PhD programs, respectively. Other postbaccalaureate pursuits included careers in pharmacy, optometry, dentistry, public health, physical therapy, nurse practitioner, and physician's assistant, accounting for an additional 21.5%. Most students electing to stop formal education at the bachelor's degree also entered fields related to health care or science, technology, engineering, and mathematics (19.5%), with only a small number of the 200 students tracked going into service or industries which lacked an association with the health-care workforce (4.5%). These student outcomes support the concept that participation in summer undergraduate research boosts efforts to populate the pipeline of future researchers and health professionals. It is also an indication that future researchers and health professionals will be able to communicate the value of research in their professional and social associations. The report also discusses best practices and issues in summer undergraduate research for students originating from rural environments.